2011
DOI: 10.1111/j.1479-8298.2011.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Life‐history traits related to diapause in univoltine and bivoltine populations of Ypthima multistriata (Lepidoptera: Satyridae) inhabiting similar latitudes

Abstract: In most temperate insects, diapause strategies and voltinism generally exhibit latitudinal clines, supporting the concept that they represent adaptations to climate. In contrast, in the satyrine butterfly Ypthima multistriata Butler, local populations with different voltinism patterns are geographically intermingled, suggesting that life-history traits related to diapause may differ even between geographically and phylogenetically close populations. In this study, we experimentally examined the critical photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
1
10
2
Order By: Relevance
“…By exploring the effects of such relaxed selection, it is possible to study the importance of ongoing selection for upholding adaptive developmental plasticity in the form of pathway‐specific regulation of life‐history traits. Some recent studies suggest that populations experiencing relaxed selection on the direct pathway show significantly reduced differences among pathways in growth and developmental rates, which indicates that this type of differentiation in bivoltine populations is contingent on ongoing selection (Noriyuki, Akiyama & Nishida ; Aalberg Haugen, Berger & Gotthard ; Välimäki, Kivelä & Mäenpää ; Välimäki et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By exploring the effects of such relaxed selection, it is possible to study the importance of ongoing selection for upholding adaptive developmental plasticity in the form of pathway‐specific regulation of life‐history traits. Some recent studies suggest that populations experiencing relaxed selection on the direct pathway show significantly reduced differences among pathways in growth and developmental rates, which indicates that this type of differentiation in bivoltine populations is contingent on ongoing selection (Noriyuki, Akiyama & Nishida ; Aalberg Haugen, Berger & Gotthard ; Välimäki, Kivelä & Mäenpää ; Välimäki et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…By exploring the effects of such relaxed selection, it is possible to study the importance of ongoing selection for upholding adaptive developmental plasticity in the form of pathway-specific regulation of life-history traits. Some recent studies suggest that populations experiencing relaxed selection on the direct pathway show significantly reduced differences among pathways in growth and developmental rates, which indicates that this type of differentiation in bivoltine populations is contingent on ongoing selection (Noriyuki, Akiyama & Nishida 2011;Aalberg Haugen, Berger & Gotthard 2012; V€ alim€ aki, Kivel€ a & M€ aenp€ a€ a 2013; V€ alim€ aki et al 2013). Moreover, it has also been suggested that sexual differences in larval growth due to selection for protandry (the earlier adult emergence of males) may be particularly affected by relaxed selection on the direct pathway (Aalberg Haugen, Berger & Gotthard 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most temperate insect species, the number of generations of the butterfly differs even among populations located at similar latitudes and altitudes. There are four types of voltinism in Japan: bivoltine with adult emergence in June and September, univoltine with adult emergence in June, univoltine with adult emergence in July, and multivoltine (Noriyuki et al, ). Bivoltine is the most common voltinism in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has a strong effect on reproduction and development rates of in sects and has been studied in different species of Lepidoptera, such as Anticarsia gemmatalis Hiibner (Noctuidae), Aricia agestis Denis & Schiffermiiller (Lycaenidae), and Ypthima multistriata Butler (Satyridae) (Burke et al 2005, Noriyuki et al 2011, Da Silva et al 2012.…”
mentioning
confidence: 99%